Benign metastasizing leiomyoma: pulmonary involvement from an uterine fibroid - Vale-Fernandes,Emídio (2016)
Benign Metastasizing Leiomyoma (BML) is a rare disorder in which uterine fibroids metastasize to distant sites. We present a case of a 57-year-old postmenopausal woman under hormone therapy with a previous total hysterectomy for uterine fibroids that performed chest radiography, for a history of weight loss, that showed multiple bilateral pulmonary nodules. The histological examination of these nodules revealed a morphological and immunohistochemical profile consistent with the diagnosis of pulmonary BML (supported by a history of primary uterine leiomyoma). The patient started treatment with tamoxifen, remaining asymptomatic and with stable pulmonary lesions.